Blood testis barrier revisited—Analysis of post‐chemotherapy germ cell tumor orchidectomy and retroperitoneal lymph node dissection specimens. Issue 4 (11th January 2021) - Gupta, Amit; Noronha, Jarin; Bakshi, Ganesh; Menon, Santosh; Pal, Mahendra; Joshi, Amit; Prabash, Kumar; Noronha, Vanita; Murthy, Vedang; Krishnattry, Rahul; Patil, Akshay; Prakash, Gagan J.
Abstract: Objective: To assess the response of chemotherapy on the primary tumor, compare it with the response in retroperitoneal disease, and study factors associated with pathological complete response. Methods: We conducted a retrospective audit of all high inguinal orchidectomies (HIOs) performed after chemotherapy between 2012 and 2019 at a tertiary cancer center in India. Patient characteristics and histopathological response were extracted from electronic medical records, and predictors of testicular disease response were assessed. Results: Of the 260 retroperitoneal lymph node dissections (RPLNDs) performed in the study period, 37 HIOs (14.23%) were carried out after chemotherapy. The median age of presentation was 28 years (16–41). Histopathology was divided into a viable tumor, mature teratoma, and necrosis/scarring. Residual disease was seen in 17 RPLND (46.0%) and 18 HIO (48.6%) specimens respectively. Of these 18, three patients had a residual viable tumor in the testis, and the remaining had a mature teratoma. Clinico‐radiological assessment showed an average reduction of 61% in testicular disease size following chemotherapy. On orchidectomy histopathological assessment, the median tumor size was 9, 4, and 1.5 cm in specimens with a viable tumor, mature teratoma, and necrosis/scarring, respectively. Conclusions: A low threshold for upfront chemotherapy in patients with a high disease burden may be considered as tumors within the testis respond to chemotherapy in more than half of the patients. Discordance rates of residual cancer in RPLND and HIO specimens exist but post‐chemotherapy tumor size in testis correlates with the presence of a residual viable tumor.